Autarkiepolitik in der Braunkohlenindustrie : Ein diachroner Systemvergleich anhand des Braunkohlenindustriekomplexes Böhlen-Espenhain, 1933 bis 1965 - Baumert, Martin (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2022)
The lignite industrial complex Böhlen-Espenhain near Leipzig was of great significance for the autarky policies of both the Third Reich and the GDR. Martin Baumert comparatively examines the impact of three different political transformations (Nazi, SBZ, GDR) on the industrial complex, which was essential to each system, focusing on changes that took place in the organization of industry and labor